2022
DOI: 10.1155/2022/2085225
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Security Analysis of Artificial Intelligence-Based Self-Driving Technologies in Saudi Arabia: A Case Study of Openpilot

Abstract: Saudi Arabia has an ambitious vision that embraces artificial intelligence (AI) technologies at a mass scale in new cities such as Neom. Self-driving has recently become one of the most important AI applications due to the advancement of sensors and AI algorithms. Given that safety is vital to the success of self-driving cars, existing infrastructures (e.g., roads and traffic signs) should be compatible with self-driving technologies. However, self-driving technologies have not been thoroughly examined in Saud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Comma.ai uses specially designed sensors and hardware modules that are integrated into vehicles in order to obtain input about surroundings and take appropriate actions. The inputs are further classified using advanced AI and machine learning/deep learning models such as convolutional neural networks (CNN) and recurrent neural networks (RNN) for sensor data processing, image classification, object detection, semantic segmentation, and motion prediction [160]. In terms of sensor fusion, they use Kalman filters and extended Kalman filters (EKF) to combine and process data from various sensors such as cameras, radars, lidars, and microcontrollers.…”
Section: Discussion and Open Issuesmentioning
confidence: 99%
“…Comma.ai uses specially designed sensors and hardware modules that are integrated into vehicles in order to obtain input about surroundings and take appropriate actions. The inputs are further classified using advanced AI and machine learning/deep learning models such as convolutional neural networks (CNN) and recurrent neural networks (RNN) for sensor data processing, image classification, object detection, semantic segmentation, and motion prediction [160]. In terms of sensor fusion, they use Kalman filters and extended Kalman filters (EKF) to combine and process data from various sensors such as cameras, radars, lidars, and microcontrollers.…”
Section: Discussion and Open Issuesmentioning
confidence: 99%
“…Many studies (Klabi, 2020;Alotaibi et al, 2022;Alharbi & Boling, 2022) have reported Saudi nationals to be associated with Toyota and major luxury car brands. Similarly, various studies (Klabi, 2020;Alsubaei, 2022;Alsghan et al, 2022) have reported non-Saudis to differ in dress, culture, language, and many aspects from Saudis and are generally overall seen to be associated with Korean, Chinese, and other car brands.…”
Section: Brand Associations Of Reference Groups and Self-brand Connec...mentioning
confidence: 98%
“…HSA is used to deal with the AV transition in terms of technology, referring to hardware and software-sensors, actuators, processors, control software, and AI algorithms-used to make vehicles autonomous. AI algorithms for real time processing, self-driving, are still being improved, as it is an evolving process [7]. Big data processing for driving must be performed in real time, i.e., fast enough in the defined time frame, known as the response time.…”
Section: Introductionmentioning
confidence: 99%